Laser Lithotripsy for the Management of Ureteric Calculus (Nepal Medical College Journal, 2024)
Urinary calculi are important problem in urology field. Ureteral stones can cause obstructive uropathy and subsequent deterioration of renal function. The minimal invasive approaches become the major source of treatment modalities with the development of lithotripsy technology. A prospective cross sectional hospital study was conducted in the Urology Department of a tertiary care hospital in Kathmandu for a period of one year (September 2022 to August 2023). A total of 118 patients attending Urology OPD and undergoing laser lithotripsy were included in the study. Ureteroscopic procedure was done using a 6.5 Fr (Wolf Inc., Germany) semirigid ureteroscope under direct endoscopic vision and once the stone was visible, fragmentation was done using Ho-YAG laser. The mean age of the patients was 35.36 ± 11.65 years with male preponderance (58.5%). The common presenting symptom was flank pain and ureteric calculus was more common in the left side (49.2%). Upper ureteric calculus (60.2%) and single stone (83.9%) were more common. Stone size